Assessing the Potential Association Between Microbes and Corrosion of Intra-Oral Metallic Alloy-Based Dental Appliances Through a Systematic Review of the Literature - Gopalakrishnan, Umarevathi; Felicita, A. Sumathi; Mahendra, Lodd; Kanji, Masroor Ahmed; Varadarajan, Saranya; Raj, A. Thirumal; Feroz, Shaikh Mohammed Abdul; Mehta, Deepak; Baeshen, Hosam Ali; Patil, Shankargouda (Frontiers in Bioengineering and Biotechnology, 2021)
Objective: Systematic review assessing the association between oral microorganisms and corrosion of intra-oral metallic alloy based dental appliances. Design: PubMed, Scopus and Web of Science were searched using keyword combinations such as microbes and oral and corrosion; microbes and dental and corrosion; microorganisms and oral and corrosion; microorganisms and dental and corrosion. Results: Out of 141 articles, only 27 satisfied the selection criteria. Lactobacillus reuteri, Streptococcus mutans, Streptococcus sanguis, Streptococcus mitis, Streptococcus sobrinus, Streptococcus salivarius, sulfate-reducing bacteria, sulfate oxidizing bacteria, Veilonella, Actinomyces, Candida albicans were found to have a potential association with corrosion of intraoral metallic alloys such as stainless steel, titanium, nickel, cobalt-chromium, neodymium-iron-boron magnets, zirconia, amalgam, copper aluminum, and precious metal alloys. Conclusion: The included studies inferred an association between oral microorganisms and intra-oral metallic alloys based dental appliances, although, it is vital to acknowledge that most studies in the review employed an in-vitro simulation of the intra-oral condition.